2013
DOI: 10.1002/ldr.2228
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular Mycorrhizal Fungi and Glomalin‐Related Soil Protein as Potential Indicators of Soil Quality in a Recuperation Gradient of the Atlantic Forest in Brazil

Abstract: This study aimed at surveying arbuscular mycorrhizal fungi (AMF) species and glomalin‐related soil protein (GRSP) to understand their role as presumable biological indicators of soil quality in an undisturbed forest site (NT) and three sites with different management histories, soil textures, and different ages of recovery after reforestation for 20 (R20), 10 (R10) and 5 years (R05). Our objective was to determine how physical, chemical and microbiological soil attributes influence AMF species distribution, to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(39 citation statements)
references
References 50 publications
5
32
0
2
Order By: Relevance
“…Both, EE‐GRSP and T‐GRSP were significantly correlated with the SOC ( Woignier et al, ), and Fokom et al () reported the regression equations as SOC (g kg −1 ) = 0.023GRSP +1.3274 ( R 2 = 0.7648). GRSP amount was positively correlated with soil bulk density but negatively correlated with moisture ( Vasconcellos et al, ). In this paper, both linear regression and stepwise regression confirmed the strong associations between GRSP (EE‐GRSP and T‐GRSP) amount and SOC, and SEM analysis showed that GRSP could be directly affected by SOC (Tab.…”
Section: Discussionmentioning
confidence: 99%
“…Both, EE‐GRSP and T‐GRSP were significantly correlated with the SOC ( Woignier et al, ), and Fokom et al () reported the regression equations as SOC (g kg −1 ) = 0.023GRSP +1.3274 ( R 2 = 0.7648). GRSP amount was positively correlated with soil bulk density but negatively correlated with moisture ( Vasconcellos et al, ). In this paper, both linear regression and stepwise regression confirmed the strong associations between GRSP (EE‐GRSP and T‐GRSP) amount and SOC, and SEM analysis showed that GRSP could be directly affected by SOC (Tab.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, to assess the effect of changes in SOC content on soil structure condition, the aggregate stability can be considered as a good indicator (Moncada et al, 2013). SOC content, nitrogen and phosphorus are some of the most important chemical soil quality indicators for soil recovery and can drive changes in the biological, chemical and physical soil attributes (Vaconcellos et al, 2013). Similar positive effects were recorded with various forms of organic matter and arbuscular mycorrhizal fungi addition (Ferreras et al, 2006;Kavdır and Killi, 2008;Yılmaz, 2011;Vaconcellos et al, 2013).…”
Section: Effects Of Different Rates Of Humic Acid (Ha) Applications Omentioning
confidence: 96%
“…Soils play a major role in providing mineral nutrients, water and a substrate to plants, and soil properties affect the health of natural and agroecosystems (Trabaquini et al, 2015;Vasconcellos et al, 2016) as well as human health (Brevik and Sauer, 2015).…”
Section: Introductionmentioning
confidence: 99%